Phantoms in the Brain: Human Nature and the Architecture of the Mind - V S Ramachandran (Harper Collins Publishers, 2008)
Using a series of case studies, 'Phantoms in the brain' introduces a strange and unexplored mental world. Ramachandran, through his research into brain damage, has discovered that the brain can react in strange ways to major physical changes.